Weighted Estimates of the Cayley Transform Method for Boundary Value Problems in a Banach Space. (4th December 2021) - Makarov, V. L.; Mayko, N. V.
Abstract: We consider the boundary value problems (BVPs) for linear second-order ODEs with a strongly positive operator coefficient in a Banach space. The solutions are given in the form of the infinite series by means of the Cayley transform of the operator, the Meixner type polynomials of the independent variable, the operator Green function, and the Fourier series representation for the right-hand side of the equation. The approximate solution of each problem is a partial sum of N (or expressed through N ) summands. We prove the weighted error estimates depending on the discretization parameter N, the distance of the independent variable to the boundary points of the interval, and some smoothness properties of the input data.